Elastic and thermodynamic properties of potentially superhard carbon boride materials - Letsoalo, T.E.; Lowther, J.E. (Сверхтвердые материалы, 2012)
Boron icosahedral structures are the basic building structures of many important hard borides and especially В₄С. The structural and thermodynamic properties of В₄С have been examined applying molecular dynamics simulation with the use of both ab initio and bond order Tersoff potentials. Various physical quantities of В₄С including the elastic constants, thermal expansion coefficients, and specific heat have been examined. Ікосаедрічні структури бору є основними будівельними конструкціями багатьох важливих твердих боридів і особливо це стосується В₄С. Досліджено структурні та термодинамічні властивості В₄С при застосуванні моделювання динаміки молекул з використанням як ab initio розрахунків, так і потенціалів Терсоффа. Розглянуті різні фізичні характериcтики В₄С, включаючи пружні константи, коефіцієнти теплового розширення і теплоємність. Икосаэдрические структуры бора являются основными строительными конструкциями многих важных твердых боридов и особенно это касается В₄С. Исследованы структурные и термодинамические свойства В₄С с применением моделирования динамики молекул, используя как ab initio расчеты, так и потенциалы Терсоффа. Рассмотрены различные физические характериcтики В₄С, включая постоянные упругости, коэффициенты теплового расширения и теплоемкость.